Kai kurie literatūros atrankos klausimai Pabaltijo respublikų rekomendacinės bibliografijos leidiniuose - Tomonis, Stasys (Knygotyra, 1972)
Recommendatory bibliography developed in analogical circumstances in the Baltic republics, though there are some peculiarities of development especially in selection of literature.Selection criteria play a decisive role in the destination and structure of recommendatory publications, but until now they have been scantily elucidated in librarian literature. Criteria may differ in language, chronology, complicacy and actuality of the literature, types and forms of publication. In a certain degree subjects of selected literature may be regarded as a criterion of selection.In the present article some analysis has been done on recommendatory publications of the Baltic republics available at the State Library of the Lithuanian SSR. For analysis were taken 71 publications of the Latvian, 28 of the Estonian and a 100 of the Lithuanian SSR. The above-mentioned analysis has shown that subjects of recommendatory publications in the Baltic republics are analogical. The greater part of the publications is on social and political subjects, then come literature and art, natural sciences, agriculture; fewer than others are publications on technical subjects. Only Estonian bibliographical indices on the subjects of technical and natural sciences exceed those of literature and arts.Selection of literature on language criterion varies in different Soviet republics. There are considerable differences also in the recommendatory publications of the Baltic republics. In recommendatory publications of the Estonian SSR in all cases only literature in the Estonian Ianguage is indicated. Such a method can hardly be regarded expedient as it considerably limits the use of recommendatory bibliography. At first in the Latvian SSR too only literature in the Latvian language was indicated, but from about 1950 all the literature was duplicated and indicated parallel in two languages – Latvian and Russian. Lately literature has been duplicated only in publications of subjects on local lore. While in other publications literature in the Russian language is given as supplementary. In recommendatory publications of the Lithuanian SSR all literature on subjects of local lore is indicated parallel in the Llthuanian and Russian languages, and in some of publications in other languages too. In order to avoid duplication of analogical issues of the USSR central libraries literature in the Lithuanian language is mostly indicated in publications on universal subjects, but in cases, when literature in the Lithuanian language is insufficient, Russian literature is indicated supplementary. Such a selection of literature under existing conditions proves to be the most valuable, though it is advisable that the central recommendatory publications should be issued in greater numbers and that they should be more accessible to the wide circles of readers in all the Soviet republics.Other criteria in selecting literature for recommendatory publications are very much alike in all the Baltic republics. But in many issues of the Lithuanian SSR there is a tendency to widen the limits of different criteria. Thus different publications include some fiction and popular-scientific books, published in the early post-war years and still of interest at present; for more extensive study in some publications are indicated books and articles dealing with research work. Even selection criterion concerning the form of issues is widening: in separate cases they include not only books and articles of periodicals, but also music pieces, prints of fine art and cinema films. The broadening of criteria in selecting literature is connected with the pressent-day tendency to the assimilation of recommendatory and scientific bibliography.Some differences in structure of recommendatory publications of the Soviet republics living under the same economic, geographic and cultural conditions prove to be result of different methods. This could be avoided by means of a wider discussion of the above problems as well as by their appropriate elucidation in literature.